SOCIAL ADJUSTMENT OF COLLEGE STUDENTS WITH DISABILITIES (Proceedings of International Conference on Special Education, 2019)
Social adjustment can be challenging to some people, especially those who were differently abled because they faced a bigger stressor. This study aim is to describe the social adjustment of college student with disabilities. This study was a qualitative-deductive study. The data of this study was collected using semi-structured interview to three informants, two of them are Deaf (hearing impairment) and the other person was physically disabled that require the use of wheel chair. Qualitative content analysis-deductive was used to analyze the data. The results in this study indicate that college student with disabilities represented some social attitudes in order to be accepted in their environments. Those attitudes were: taking part in social activities in the faculty, offering helps to others, showing empathy to their friends’ conditions. However, there were some attitudes that were not optimally shown, those were: appreciating the values and others’ opinion, and following the rules in the faculty. There were disabled student(s) that indicated having high passion to finish their study.